Building an Islamic Culture of Leadership Based on Principles of Mercy for All Creation (Rahmatan Lil ‘Alamin) - Nur Kholis (Jurnal Hikmatuna, 2015)
The primary purpose of this paper is to offer an approach to building a culture of leadership based on the Prophet Muhammad’s teaching of love.Since people are strongly motivated by values they deeply adhere to, the paradigms used as rationale for this paper embody views of leaders asmotivators and values transformation as their main task. It is argued that the Prophet Muhammad’s teaching of love needs to be cultivated in anIslamic school community. The paper presents discussion on trans-rational values as the contributing factor to this view, and the main argument centres on the discussions of the Prophet Muhammad’s teaching of love and its application in developing a culture of leadership in Islamic schools.